1999
DOI: 10.1093/jat/23.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Aeromedical, Toxicopharmacological, and Analytical Aspects*,†

Abstract: IMelatonin, a pineal hormone present in the blood of humans and other species, has a distinct diurnal variation in its biosynthesis and, therefore, in its concentration. This variation has suggested the possibility of a regulatory function in day/night-dependent physiological processes such as sleep and has led scientists to explore the effects of administered melatonin on the modulation of circadian rhythms. For the self-treatment of sleep disorders and other benefits, melatonin use has been extolled to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 78 publications
0
8
0
2
Order By: Relevance
“…Normally, melatonin production occurs during the dark phase of the day. The distinct diurnal variation has suggested the possibility of a regulatory function of melatonin in day/night-dependent physiologic processes, such as sleep (5). Recently, laboratory studies have also shown the antiproliferative, antioxidative, and immunostimulatory actions of melatonin (6).…”
Section: Introductionmentioning
confidence: 99%
“…Normally, melatonin production occurs during the dark phase of the day. The distinct diurnal variation has suggested the possibility of a regulatory function of melatonin in day/night-dependent physiologic processes, such as sleep (5). Recently, laboratory studies have also shown the antiproliferative, antioxidative, and immunostimulatory actions of melatonin (6).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown to act as an antioxidant (Reiter et al, 1997; Reiter, 1998). The synthesis of melatonin varies during the day and at night (Sanders et al, 1999), the maximal amount being secreted in the dark at night (Borjigin et al, 1999). Other factors, such as ischemia, are known to affect production of melatonin; for example, reduced production of melatonin is known to occur in various ischemic conditions, such as coronary artery disease (Sakotnik et al, 1999), and administration of exogenous melatonin under ischemic conditions has proved useful because of its protective effects (Cuzzocrea et al, 2000).…”
mentioning
confidence: 99%
“…The synthesis of melatonin varies during the day and at night [13], maximum amount being secreted in the dark at night [25]. Melatonin levels decline with age [8].…”
Section: Introductionmentioning
confidence: 99%